MOLECULAR DYNAMICS SIMULATIONS OF MODY2 MUTATED GLUCOKINASE STRUCTURES REVEALED SIGNIFICANT CONFORMATIONAL VARIATIONS EXPLAINING REASONS FOR HYPERGLYCEMIC CONDITION - Y. NANDA KUMAR; K. KALPANA; K. VENKATESWARA SWAMY; P.V.G.K.SARMA; M. BHASKAR (International Journal of Pharma and Bio Sciences, 2012)
Glucokinase (GK) involves in the phosphorylation of Glucose in pancreatic β-cells and liver to maintain normal blood glucose levels. Inactivating and activating mutations in GK gene can influence the affinity for glucose and leads to altered glucose levels in blood causing Maturity Onset Diabetes of the Young2 (MODY2) condition. In this study, impact of 42 MODY2 mutations on GK conformation was studied using molecular dynamics study. Simulations were carried out for intact and mutated GK structures and the correlation of their energy and RMSD (Root Mean Square Deviation) values showed significant differences. The PDBSum analysis of simulated structure revealed the clear variation in the conformation of mutated GK structures where they showed increased g-turns, decreased b-turns and more helix-helix interactions with respect to intact GK. Such a conformational variations could affect the activity of GK and may results in hyperglycemic condition in MODY2 patients